Basic guide to anatomy and physiology for dental care professionals - Hollins, Carole; Wiley eBooks (Chichester, West Sussex : John Wiley & Sons, 2012)
The Basic Guide to Anatomy and Physiology for Dental Care Professionals introduces the fundamentals of human anatomy and physiology to the student Dental Care Professional. Written in a clear, accessible style, it provides dental nurses, hygienists, therapists and clinical dental technicians with essential grounding in the head and neck area, as well as all the body systems that have implications for the DCP when things go wrong. Beginning with a definition of anatomy and physiology, and with all the basics of cell, tissue and organ biology, this Basic Guide covers:the cardi.
Basic biology -- Cardiovascular system -- Respiratory system -- Digestive system -- Nervous system -- Oral embryology and histology -- Skull and oral anatomy -- Tooth anatomy -- Periodontal anatomy -- Salivary glands.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Anatomy; Physiology; Dentistry; Mouth -- Anatomy; Teeth -- Anatomy; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Anatomy; Dentistry; Physiology; Anatomy; Physiological Phenomena; Stomatognathic System -- anatomy & histology; Electronic books